2013
DOI: 10.1111/acer.12143
|View full text |Cite
|
Sign up to set email alerts
|

BMI But Not Stage or Etiology of Nonalcoholic Liver Disease Affects the Diagnostic Utility of Carbohydrate‐Deficient Transferrin

Abstract: An elevated BMI reduces the diagnostic utility of CDT at higher alcohol intake in subjects with CLD using the standardized method. In a hepatology outpatient setting, this assay is likely to be useful to confirm suspicion of heavy drinking in subjects who are not overweight, but cannot reliably identify moderate drinkers or heavy drinkers who are overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
2
8
2
Order By: Relevance
“…Our results conflict with those in a recent report, where di-tri bridging was not found in a sample of 254 liver disease patients, 48 of whom had biopsy-confirmed cirrhosis (Fagan et al, 2013). These authors speculated that di-tri bridging might only occur in patients with decompensated cirrhosis, but among cirrhotic subjects we did not find a strong link to cirrhosis severity as estimated by MELD and CTP scores.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results conflict with those in a recent report, where di-tri bridging was not found in a sample of 254 liver disease patients, 48 of whom had biopsy-confirmed cirrhosis (Fagan et al, 2013). These authors speculated that di-tri bridging might only occur in patients with decompensated cirrhosis, but among cirrhotic subjects we did not find a strong link to cirrhosis severity as estimated by MELD and CTP scores.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously investigated the diagnostic utility of %CDT in patients with liver disease, and found that heavy drinkers with a BMI in the overweight or obese range had significantly lower %CDT values than lean heavy drinkers [14]. The current study extends these findings by confirming the results in a larger group of subjects with confirmed heavy alcohol consumption and by showing that the effect of BMI is independent of other clinical variables.…”
Section: Discussionsupporting
confidence: 84%
“…CDT analysis was performed on a Waters HPLC System (Waters Corporation Milford MA USA) as previously described [14]. The currently accepted laboratory reference value indicative of heavy drinking is %CDT > 1.7 [3].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations